2018
DOI: 10.15252/embj.201798556
|View full text |Cite
|
Sign up to set email alerts
|

PTRN‐1/CAMSAPpromotesCYK‐1/formin‐dependent actin polymerization during endocytic recycling

Abstract: Cargo sorting and membrane carrier initiation in recycling endosomes require appropriately coordinated actin dynamics. However, the mechanism underlying the regulation of actin organization during recycling transport remains elusive. Here we report that the loss of PTRN-1/CAMSAP stalled actin exchange and diminished the cytosolic actin structures. Furthermore, we found that PTRN-1 is required for the recycling of clathrin-independent cargo hTAC-GFP The N-terminal calponin homology (CH) domain and central coile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…Through confocal stack imaging of intestinal epithelial cells from intact living animals ( Fig 1B), we found that, in both sid-3 mutants, the number and size of hTAC-GFP-labeled intracellular structures increased significantly (~9-fold increase in total area) ( Fig 1C-1C''). This phenotype is typical of basolateral recycling mutants [5,12,[28][29][30]. We further assayed the accumulation of FGT-1, the worm homolog of another clathrin-independent recycling cargo, GLUT1 [8], and observed that SID-3 deficiency led to substantial intracellular aggregation of FGT-1-positive structures (~7.8-fold increase in total area) (S1A and S1A ' Fig).…”
Section: Loss Of Sid-3 Causes Endocytic Recycling Defectsmentioning
confidence: 82%
“…Through confocal stack imaging of intestinal epithelial cells from intact living animals ( Fig 1B), we found that, in both sid-3 mutants, the number and size of hTAC-GFP-labeled intracellular structures increased significantly (~9-fold increase in total area) ( Fig 1C-1C''). This phenotype is typical of basolateral recycling mutants [5,12,[28][29][30]. We further assayed the accumulation of FGT-1, the worm homolog of another clathrin-independent recycling cargo, GLUT1 [8], and observed that SID-3 deficiency led to substantial intracellular aggregation of FGT-1-positive structures (~7.8-fold increase in total area) (S1A and S1A ' Fig).…”
Section: Loss Of Sid-3 Causes Endocytic Recycling Defectsmentioning
confidence: 82%
“…Thus, the combined defects in NOCA-1 and PTRN-1 localization we observed upon PAR-6 depletion may partially explain the growth defects. The roles of PTRN-1 may not be limited to microtubule regulation, as a recent study demonstrated that PTRN-1 stimulates actin polymerization during endocytic recycling in the intestine ( Gong et al, 2018 , p. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CCR2B and β2AR signaling induces the phosphorylation of FLNa that promotes receptor recycling [70]. Several other actin regulators play a role in the biogenesis of tubular membrane carriers by regulating actin assembly, disassembly and/or bundling; these include the Cdc42-guanine nucleotide exchange factor FGD6 [74], the regulator of endocytic recycling EHBP-1 [75], and formins [76,77].…”
Section: Actin In the Formation And Stabilisation Of Tubular Domains mentioning
confidence: 99%